THE IMPACT OF EVENT MARKETING ON BUILDING BRAND AWARENESS FOR FASHION CUSTOMERS - Rachmadhian, Annissa Karni; Chaerudin, Rendra (UI Scholars Hub, 2021)
The growth of Small Medium and Enterprises (SMEs) business is one of the main keys to an economy’s vitality. SMEs are known to play a major role in creating wealth, given their place in the economy. As time goes by, numerous strategies have been done by the company to promote their products. One of the innovations that a company does to introduce the product and build awareness among the target market is through event marketing strategy. SMEs business can use this marketing strategy to increase their brand awareness. The purpose of this paper is twofold: to analyse the effect of event marketing strategy to brand awareness customer apparel industry in Bandung, and to give a design recommendation. The result shows that event marketing has a positive impact on brand awareness. Several important aspects from an event that customer wants are an innovative, integrated enterprise event. Event marketing should be well designed in order to make the memorable experience for the customer. This paper will be useful for marketers, business owners and in particular for other parties involved in fashion SMEs to understand the impact of event marketing and its importance on building brand awareness for fashion customers. Ultimately, once they can implement this event marketing strategy in their businesses, they are able to design the strategy of event marketing to build customers’brand awareness.